1969
DOI: 10.1021/i260032a003
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrocracking. Hydrocracking of a Low Temperature Coal Tar

Abstract: The hydrocracking of a low temperature coal tar in a batch autoclave over a dual-functional catalyst containing sulfides of nickel and tungsten supported on silica-alumina yielded 75% gasoline of premium grade. The dual-functional catalyst gave better product distribution with respect to gasoline, while the refining catalyst containing sulfides of tungsten and nickel on alumina gave a better product distribution with respect to the yield and quality of diesel oil. The dual-functional catalyst exhibited higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1969
1969
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…The tar, the neutral tar, the refined tar, and the tar fraction were used as feed materials (Table I). The catalyst used was the same as reported by Qader and Hill (1969).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tar, the neutral tar, the refined tar, and the tar fraction were used as feed materials (Table I). The catalyst used was the same as reported by Qader and Hill (1969).…”
Section: Methodsmentioning
confidence: 99%
“…Equipment and Experimental Procedure. The equipment and experimental procedure described by Qader and Hill (1969) were employed for the experimental work and to evaluate the products. The yields of liquid plus gaseous product from different coal tar fractions were almost 100% by volume of the feed material (Table II).…”
Section: Methodsmentioning
confidence: 99%
“…There are few studies on real reaction mechanisms in the literature, and those that exist are limited to asphaltenes in VR hydrocracking [173]. Some studies have reported that hydrocracking of heavy oil is affected by reaction conditions such as temperature, initial H 2 pressure and H 2 S partial pressure [174][175][176].…”
Section: Hydrocracking Reaction Mechanismsmentioning
confidence: 99%
“…22 Generally, the operation temperature of hydrocracking and catalytic cracking process is generally higher than 300 C, which causes a higher coking rate and a large amount of C 1 -C 4 light hydrocarbon. [23][24][25][26][27] However, the composition of jet fuel is mostly C 8 -C 15 , [28][29][30][31][32] and the content of aromatics is relatively low. In general, the heat value decreased in order alkane > cycloalkane > aromatic.…”
Section: Introductionmentioning
confidence: 99%